Complicance checklist for the propulsion system. - Paulo Henrique Barcelos (2003)
During the aircraft certification process, it is necessary to guarantee the design, integration and installation for safety by showing compliance with the certification and safety requirements. In order to be granted with the Type Certification for that specific aircraft in development, the applicant must go through the certification regulations, and demonstrate compliance for every requirement stated in the RBHA/FAR/JAR 25 regulation. The means of compliance for every single requirement shall be defined in the early stage of the aircraft designing process and structured in a format of a "compliance check list". The primary intent of this process is to follow the aircraft design and development phases and check that all safety and certification requirements are met. Also the methods of compliance (design review / drawing, analysis, flight tests, ground tests, lab tests, qualification tests, simulations, inspections, similarities) are assigned, as part of this means of compliance process and these are to get early commitment of acceptability of the way that the aircraft is designed and developed from the certification authorities. The intent of this report is to describe a certification tool that supports the aircraft propulsion system design and development by defining an acceptable means of compliance to the RBHA/FAR/JAR 25 regulation - Subpart E, based on a generic aircraft with high-bypass turbofan installed engines (twin). Some historical service accidents summaries caused by propulsion system malfunctions and failures are reported within this document in order to highlight the importance of the accomplishment of this certification process. Many of these accidents records were used to improve the inadequate and past old requirements and replacing/revising to the new ones to minimize the hazard level of the airplane. During the aircraft certification process, it is necessary to guarantee the safety through accomplishing the requirements. Therefore, the regulations authorities and the applicant do the technical work of demonstrating compliance to the requirements in the certification basis for the project, which project is managed in accordance with the Project Specific Certification Plan.